Computer model for weight loss and energy conservation in a fresh-produce refrigerated store - Devres, Y.O.; Bishop, C.F.H. (Elsevier BV, 1995)
Abstract A computer model is described for calculating energy consumption and moisture loss. The model uses data from an actual potato store in the Cambridge region of the UK. The differences between actual and calculated power consumption values for 1989–1990 and 1990–1991 seasons are +1·0% and −2·3% respectively. For the whole storage season, the weight losses are 5·09% and 5·02% for the 1989–1990 and 1990–1991 seasons, respectively.